2011
DOI: 10.1111/j.1096-0031.2010.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics and divergence times of Papilioninae (Lepidoptera) with special reference to the enigmatic genera Teinopalpus and Meandrusa

Abstract: Phylogenetic relationships of 18 genera of the swallowtail subfamily Papilioninae, four genera of Parnassiinae, and the monobasic Baroniinae are inferred based on 94 morphological characters and 5616 bp DNA from seven genes (16S, COI, COII, ND1, ND5, EF-1 alpha and wingless). Bayesian likelihood analyses show that Baroniinae are the sister of a clade comprising Parnassiinae and Papilioninae. Four Papilioninae tribes are recognized, Leptocircini, Teinopalpini, Papilionini and Troidini, with Leptocircini being t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(114 citation statements)
references
References 78 publications
11
102
0
1
Order By: Relevance
“…Recent analyses indicate that several butterfl y families younger than the Hesperiidae (based on phylogenies reported in several recent studies, such as Heikkilä et al, 2011;see land et al, 2015), Lycaenidae, as sister to the Riodinidae, should be similar in age. In addition, the age of the older family Papilionidae was recently estimated at 68 (53-87) Ma (Simonsen et al, 2011). Clearly, this cannot be true at the same time, with the youngest family at the root.…”
Section: Importance Of This Fossil For Determining the Time Dimensionmentioning
confidence: 99%
“…Recent analyses indicate that several butterfl y families younger than the Hesperiidae (based on phylogenies reported in several recent studies, such as Heikkilä et al, 2011;see land et al, 2015), Lycaenidae, as sister to the Riodinidae, should be similar in age. In addition, the age of the older family Papilionidae was recently estimated at 68 (53-87) Ma (Simonsen et al, 2011). Clearly, this cannot be true at the same time, with the youngest family at the root.…”
Section: Importance Of This Fossil For Determining the Time Dimensionmentioning
confidence: 99%
“…(6) Plausible explanations for the distributions of widespread groups that show multiple disjunctions often involve a combination of vicariance and LDD (e.g. Gamble et al 2011;Krosch et al 2011;Simonsen et al 2011;Springer et al 2012;Thomas et al 2014;Pyron 2014;Thornhill et al 2015). In fact, such results are so common that the default expectation for disjunctions in such taxa might be that they are not fully explained by either pure vicariance or pure LDD scenarios.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Condamine et al (2012) reconstructed Aristolochiaceae as the ancestral host for Papilionidae, pointing to the importance of the group for studying co-evolution, especially the plant-butterfly interaction. Caterpillars of a dozen Papilionidae genera (Allancastria, Archon, Battus, Cressida, Euryades, Losaria, Luehdorfia, Ornithoptera, Pachliopta, Parides, Pharmacophagus, Troides) feed on Aristolochiaceae and the majority of the tribe Troidini on the genus Aristolochia (Parsons 1996a(Parsons , 1996bSimonsen et al 2010). The most prominent species known to feed on species of subg.…”
Section: Introductionmentioning
confidence: 99%
“…Both morphological (Huber 1960(Huber , 1985González and Stevenson 2002) and molecular phylogenetic studies (Ohi-Toma et al 2006;Bliss et al 2013) have shown that Pararistolochia occurs not only in Africa, but that species from Australasia have to be included as well. Aristolochiaceae are important host plants for various genera of the family Papilionidae (Lepidoptera) (Simonsen et al 2010). In addition, Condamine et al (2012) reconstructed Aristolochiaceae as the ancestral host for Papilionidae, pointing to the importance of the group for studying co-evolution, especially the plant-butterfly interaction.…”
Section: Introductionmentioning
confidence: 99%